Ni based nano MOF and graphene composite for facile, highly efficient and stable non-enzymatic electrochemical sensing of hydrogen peroxide - Brito-Ramírez, T (Elsevier B.V., 2025)
This study presents a facile and ex-situ approach for the synthesis of a nickel-based Metal-Organic Framework and Graphene-based material (G/nanoMOF-Ni) nanocomposite, utilizing a sonication process for highly efficient electrochemical detection of H2O2. The amperometric sensor, based on a glassy carbon electrode modified with the hybrid material (GCE/G/nanoMOF-Ni), is fabricated through a simple and rapid drop-casting technique. The electrochemical performances of various composites with varying weight proportions of nanoMOF-Ni and G are studied, observing that there is no decrease in the active sites of nanoMOF-Ni in the presence of a high percentage of G in the hybrid material. Electrochemical analyses revealed that the GCE/G/nanoMOF-Ni sensor exhibits excellent catalytic activity for the oxidation of H2O2, with a sensitivity of 78.4 μAmM⁻¹cm⁻², rapid response time, and a broad linear detection range from 1.0 mM to 37 mM. Furthermore, the electrochemical sensor demonstrates good stability over time under ambient conditions and remarkable selectivity against various interferences. © 2025 Elsevier B.V.